2002
DOI: 10.1159/000064159
|View full text |Cite
|
Sign up to set email alerts
|

Connectional Evidence for Dorsal and Ventral V3, and Other Extrastriate Areas in the Prosimian Primate, <i>Galago garnetti</i>

Abstract: Previously we described patterns of connections that support the concept of V3 in small New World marmoset monkeys, three species of larger New World monkeys, and two species of Old World macaque monkeys. Here we describe a pattern of V1 connections with extrastriate visual cortex in Galago garnetti (also known as Otolemur garnetti) that demonstrates the existence of a V3 in a strepsirhine (prosimian) primate. Injections of fluorochromes or cholera toxin subunit-B (CTB) in V1 labeled cells and terminals in ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
72
1

Year Published

2002
2002
2013
2013

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 53 publications
(78 citation statements)
references
References 81 publications
5
72
1
Order By: Relevance
“…The view presented in the Rosa et al's commentary is based on retinotopic maps from Rosa's group and connection patterns from Angelucci's group, with all of the work being conducted in marmoset monkeys. As we presented in the original review not only does a large body of anatomical and mapping data in several species other than marmoset support the Lyon & Connolly interpretation of a V3d [2][3][4][5][6][7][8][9][10][11][12][13][14][15], the original work that led Jon Kaas and me to the re-interpretation of a V3d in place of DM was with marmosets as well [16].…”
mentioning
confidence: 83%
See 1 more Smart Citation
“…The view presented in the Rosa et al's commentary is based on retinotopic maps from Rosa's group and connection patterns from Angelucci's group, with all of the work being conducted in marmoset monkeys. As we presented in the original review not only does a large body of anatomical and mapping data in several species other than marmoset support the Lyon & Connolly interpretation of a V3d [2][3][4][5][6][7][8][9][10][11][12][13][14][15], the original work that led Jon Kaas and me to the re-interpretation of a V3d in place of DM was with marmosets as well [16].…”
mentioning
confidence: 83%
“…In summary, it seems likely that differences in the localization of the outer border of dorsal V2 is the primary reason for the very different conclusions regarding V3d and DM following the analysis of connection patterns [6][7][8]16,24]. Even while more anatomical studies would certainly help in evaluating whether or not there is a DM or a V3d immediately adjacent to the outer border of dorsal V2, the preponderance of evidence from imaging of retinotopic maps in monkeys and humans [1] is overwhelmingly in favour of V3d.…”
mentioning
confidence: 99%
“…In early studies from our laboratory, we did not recognize V3 and included the territory of V3 in other visual areas (see Kaas and Lyon, 2001). However, now we feel that the issue is largely resolved (Lyon, 2007), as a series of anatomical studies provided strong evidence for V3 (including ventral and dorsal halves) in prosimian galagos (Lyon and Kaas, 2002a) four species of New World monkeys 2002b;Lyon, et al, 2002) and Old World macaque monkeys (Lyon and Kaas, 2002c). V1 and V2 both have connections that associate them with both the dorsal and ventral visual streams, but more of their outputs are directed into the ventral stream (Kaas, 2004a).…”
Section: Cortical Areas Of the Dorsal And Ventral Streamsmentioning
confidence: 99%
“…Although the primary visual cortex (V1) receives feedback connections from higher visual areas (Girard et al, 2001;Lyon & Kaas, 2002), its spatial organization is closely tie to the afferent inputs from the retino-geniculate pathway. Brain-lesion and brain-imaging studies have demonstrated a retinotopic organization in V1 (e.g.…”
Section: Retinotopic Organization In the Visual Cortexmentioning
confidence: 99%